Identification of a macroscopic anisotropic damage model using digital image correlation and the equilibrium gap method - Crouzeix, Laurent; Périé, Jean-Noël; Collombet, Francis; Douchin, Bernard (European Journal of Computational Mechanics, 2010)
The aim of the work is to demonstrate how an anisotropic damage model may be identified from full field measurements retrieved during a heterogeneous test. The example of a biaxial test performed on a 3D C / C composite is used. In a first step, the displacement fields measured by classical Digital Image Correlation are used as input data of a finite difference version of the Equilibrium Gap Method. A benefit from unloadings (assumed to be elastic) is shown to retrieve a damage law. In a second step, inelastic strains can be assessed from the total measured strain and the elastic estimated strains. The constitutive parameters relative to the inelastic part of the model are then identified.